Intragenic deletions of ALDH7A1 in pyridoxine-dependent epilepsy caused by Alu-Alu recombination. (1st September 2015) - Mefford, Heather C.; Zemel, Matthew; Geraghty, Eileen; Cook, Joseph; Clayton, Peter T.; Paul, Karl; Plecko, Barbara; Mills, Philippa B.; Nordli, Douglas R.; Gospe, Sidney M.
Abstract : Objective: To investigate the role of intragenic deletions of ALDH7A1 in patients with clinical and biochemical evidence of pyridoxine-dependent epilepsy but only a single identifiable mutation in ALDH7A1 . Methods: We designed a custom oligonucleotide array with high-density probe coverage across the ALDH7A1 gene. We performed array comparative genomic hybridization in 6 patients with clinical and biochemical evidence of pyridoxine-dependent epilepsy but only a single detectable mutation in ALDH7A1 by sequence analysis. Results: We found partial deletions of ALDH7A1 in 5 of 6 patients. Breakpoint analysis reveals that the deletions are likely a result of Alu-Alu recombination in all cases. The density of Alu elements within introns of ALDH7A1 suggests susceptibility to recurrent rearrangement. Conclusion: Patients with clinical pyridoxine-dependent epilepsy and a single identifiable mutation in ALDH7A1 warrant further investigation for copy number changes involving the ALHD7A1 gene.